Degradasi Lingkungan Sebagai Pedagogi Moral: Pembacaan Pendidikan Al-Qur’an terhadap Q.S. Ar-Rūm (30) : 41 - Mutia Rahmawati; Mahyuddin Barni (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2026)
Environmental degradation has increasingly become a critical issue within contemporary education, yet it is often approached from technical and scientific perspectives with limited attention to moral and spiritual dimensions. This article examines environmental degradation as a form of moral pedagogy through a Qur’anic educational reading of Q.S. ar-Rūm (30):41. The study aims to explore how the Qur’an conceptualizes environmental damage as a moral consequence of human actions and how this perspective can inform Islamic educational thought. Employing a qualitative and conceptual research design, this study is based on textual analysis of classical and contemporary Qur’anic exegesis, supported by relevant literature in Islamic education and moral philosophy. The analysis reveals that Q.S. ar-Rūm (30):41 frames environmental corruption as an educational sign that functions pedagogically to awaken moral awareness, ethical responsibility, and human accountability before God. Environmental crises are not merely physical phenomena, but moral lessons intended to correct human behavior and restore ethical balance. This study argues that positioning environmental degradation as moral pedagogy enriches Islamic education by integrating ecological awareness with Qur’anic moral reasoning. The findings contribute to the development of value-based environmental education grounded in Qur’anic epistemology and offer a conceptual framework for strengthening moral and ecological consciousness in Islamic educational discourse.